Generic remedies in the pharmaceutical market: an integrative approach (Research, Society and Development, 2022)
A generic drug represents a pharmaceutical drug that contains the same chemical substance as a drug originally protected by chemical patents. Generic drugs can be sold after the original drug patents expire. As the active chemical substance is the same, the medical profile of generics is equivalent in performance. Thus, the objective of this research was to verify in the literature in an integrative way the importance of generic drugs in the pharmaceutical market. This is an exploratory, descriptive research, which will be carried out in the form of an integrative literature review and during the search, a total of 250 abstracts were found distributed differently in relation to the databases: Google academic (140), ScieLO (17) and Science Direct (93), leaving 10 articles selected by this study after using the inclusion criteria. The speed of appearance on the market and the acceptance of generics varied according to the pharmacological group. The Generics Law changed the dynamics of the pharmaceutical market. Future studies should examine the ongoing changes in the market as consumers gain greater confidence in generic products and manufacturers develop new marketing strategies.